ESTILO DE VIDA E DESEMPENHO COGNITIVO EM IDOSOS DO NATIONAL HEALTH AND NUTRITION EXAMINATION SURVEY (NHANES) 2011-2012 E 2013-2014 - Vidal Ferreira, Naomi; Gomes Gonçalves, Natalia (Revista Formadores, 2023)
.